Advantages, disadvantages and optimization of organ-sparing methods for uterine fibroids treatment - A. L. Tikhomirov; V. V. Kazenashev; O. V. Maksimova; M. V. Maminova; N. L. Davydenko; N. V. Rurua; T. A. Sonina (IRBIS LLC, 2020)
Introduction. Uterine fibroids (UF) are benign monoclonal hormone-depended tumors originating from smooth myocytes of cervix or body uterus affecting up to 29 % of women aged 15-45 years worldwide. Taking into account the current demographic situation and annually increasing tendency for pregnancy planning at older reproductive age, an organ-sparing strategy is becoming a first-priority approach for UF treatment.Aim: to investigate efficiency of selective progesterone receptors modulators (SPRM) for UF treatment in women of reproductive age.Materials and Methods. A prospective cohort study involved 40 patients with UF at average age of 39.3 ± 5.8 years. Using simple randomization, the patients were divided into 2 groups per 20 subjects in each. The average age of the patients was comparable and comprised 38.15 ± 5.65 and 40.5 ± 5.8 years in groups 1 and 2, respectively (p = 0.203). In both groups, after assessing liver function tests in accordance with the instructions, a treatment course with SPRM group drug (ulipristal acetate) was used at a daily dose of 5 mg for 84 days (1 course) with an interval until the onset of second menstruation after drug withdrawal. Group 1 and group 2 subjects received 2 and 3 therapy courses, respectively. After each course, patients underwent control ultrasound examinations (UE) by analyzing uterus volume and diameter of dominant myomatous node along with liver tests. A temporal quantitation of the difference between UF and dominant node two sizes as well as the maximum uterine volume size and effect size assessment was expressed as the difference of means (Δ) with a 95 % confidence interval (CI).Results. Based on UE data, the uterus size in group 1 was enlarged to an average of 129.49 ± 75.57 cm3, the maximum size of dominant node was 38.9 ± 17.38 mm; in group 2, the uterus was as large as 294.83 ± 161.37 cm3 with maximum size of the dominant node of 53.33 ± 25.48 mm. After therapy in group 1, dominant node size was significant regressed: after therapy course 1 an effect size of quantitated difference between UF two sizes and the dominant node (Δ) was 8.70 (4.11; 13.29) mm (p < 0.001). After therapy course 2 vs. therapy course 1, a size stabilization (Δ) was noted comprising 1.00 (-1.39; 3.39) mm (p = 0.390); the total effect (Δ) was 9.67 (-14.59; -4.75) mm (p <0.001). In group 2, after therapy course 1, the dominant node also regressed, with effect size (Δ) of 9.49 (7.08; 11.89) mm (p = 0.001). The effect (Δ) after therapy course 2 vs. therapy course 1 in group 2 was more prominent reaching 10.74 (5.86; 15.61) mm (p = 0.001). However, after therapy course 3, a larger node size was observed compared to therapy course 2 - (Δ) 8.25 (0.67; 15.83) mm (p = 0.329). Despite the lack of pronounced negative dynamics, based on medical indications 9 patients in group 2 underwent uterine artery embolization to prevent disease relapse.Conclusion. SPRM therapy can be used both as an independent means for MM therapy and in combination with surgical interventions. Such an approach allows for some women to become pregnant without preceding myomectomy, whereas for those approaching age-related menopause to avoid surgical treatment and gently enter natural postmenopause. Currently, conservative and surgical treatment methods for leiomyomas should complement each other to achieve the best clinical outcomes.